COLORECTAL POLYPOSIS IN AMBULANCE SITUATION (CLINICAL OBSERVATION) - D. P. Puzanov (Инновационная медицина Кубани, 2019)
In the present study we demonstrated two clinical cases with patients treated for colorectal polyposis. Patients were treated out-patiently in the diagnostic center. Performed diagnostic and treatment methods encouraged full recovery in short terms without patient hospitalization and could be recommended for wide introduction in the clinic.